2022
DOI: 10.1007/s00330-022-08809-0
|View full text |Cite
|
Sign up to set email alerts
|

Background parenchymal enhancement in contrast-enhanced MR imaging suggests systemic effects of intrauterine contraceptive devices

Abstract: Objectives Levonorgestrel-releasing intrauterine contraceptive devices (LNG-IUDs) are designed to exhibit only local hormonal effects. There is an ongoing debate on whether LNG-IUDs can have side effects similar to systemic hormonal medication. Benign background parenchymal enhancement (BPE) in dynamic contrast–enhanced (DCE) MRI has been established as a sensitive marker of hormonal stimulation of the breast. We investigated the association between LNG-IUD use and BPE in breast MRI to further ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Common side effects include irregular bleeding, abdominal and pelvic pain, acne, ovarian cysts, and headache, and adhesion to or perforation of the uterine lining is possible [ 2 ]. While the effects of hormonal IUDs should theoretically be localized to the uterine area, studies have suggested they have more systemic impact than anticipated, including hormonal stimulation of breast tissue [ 3 , 4 ].…”
Section: Hormonal Contraceptivesmentioning
confidence: 99%
“…Common side effects include irregular bleeding, abdominal and pelvic pain, acne, ovarian cysts, and headache, and adhesion to or perforation of the uterine lining is possible [ 2 ]. While the effects of hormonal IUDs should theoretically be localized to the uterine area, studies have suggested they have more systemic impact than anticipated, including hormonal stimulation of breast tissue [ 3 , 4 ].…”
Section: Hormonal Contraceptivesmentioning
confidence: 99%